Improved impact performance of marine sandwich panels using through-thickness reinforcement: Experimental results - Baral, N.; Cartié, Denis D. R.; Partridge, Ivana K.; Baley, C.; Davies, P. (Elsevier Science B.V., Amsterdam., 2010)
This paper presents results from a test developed to simulate the water impact (slamming) loading of sandwich boat structures. A weighted elastomer ball is dropped from increasing heights onto rigidly supported panels until damage is detected. Results from this test indicate that honeycomb core sandwich panels, the most widely used material for racing yacht hulls, start to damage due to core crushing at impact energies around 550 J. Sandwich panels of the same areal weight and with the same carbon/epoxy facings but using a novel foam core reinforced in the thickness direction with pultruded carbon fibre pins, do not show signs of damage until above 1200 J impact energy. This suggests that these will offer significantly improved resistance to wave impact. Quasi-static test results cannot be used to predict impact resistance here as the crush strength of the pinned foam is more sensitive to loading rate than that of the honeycomb core.
Keywords: Honeycomb; Three-dimensional reinforcement; Impact behaviour; Mechanical testing